Quality of Life and Characteristics of Colostomy Patients - Kusman Ibrahim, SKp., MNS., PhD; Ayu Prawesti Priambodo; Aan Nur’aeni; Sri Hendrawati (Universitas Airlangga, 2017)
Introduction: Colostomy imposed multiple impacts on the patient’s life including physical, psychological, social, and spiritual. This study aims to identify the level of quality of life as well as to examine the differences of quality of life among colostomy patients with regards to certain demographic characteristics.Methods: This study used a cross-sectional and descriptive analytical approach. Seventy-one colostomy patients were recruited purposively to participate in the study. The studied variables included quality of life and demographic characteristics. The data was collected by using the WHO Quality of Life – BREF instrument. One-way ANOVA and an independent t-test were employed to analyse the differences in quality of life with regards to certain demographic characteristics.Results: The study found that the majority of subjects perceived that their level of quality of life ranged between very low to moderate (77.4%). Satisfaction with support from friends was rated as the highest item of quality of life, whereas satisfaction with sexual relationships was rated as the lowest item of quality of life. There was no significant difference in the patients’ quality of life with regards to age group, educational background, occupation, length of being ostomate, sex, and other health problems.Conclusions: The study implied that nurses need to realise and pay attention to multiple aspects of stoma patient’s quality of life. Nursing care should not merely focus on stoma care but also holistically consider on meeting sexual needs, as well as the psychological, social, and spiritual needs of the patients.